On Callistocypris thailandensis sp. nov. (Ostracoda, Crustacea) from Thailand - Savatenalinton, Sukonthip; Martens, Koen (Zootaxa, 2013)
Callistocypris thailandensis sp. nov. is here described from terrestrial habitat in Khao Yai National Park, Nakhon Ratchasima province, Thailand. The new species differs from the other three Callistocypris species in the shape of carapace, the presence of strong longitudinal ridges on the ventral part of the valves and the chaetotaxy of several limbs. Zoogeo-graphy and ecology of the genus are briefly discussed.